Effect of Instructions on Selected Jump Squat Variables. Issue 9 (September 2016) - Talpey, Scott W.; Young, Warren B.; Beseler, Bradley
Abstract : Abstract: Talpey, SW, Young, WB, and Beseler, B. Effect of instructions on selected jump squat variables. J Strength Cond Res 30(9): 2508–2513, 2016—The purpose of this study was to compare 2 instructions on the performance of selected variables in a jump squat (JS) exercise. The second purpose was to determine the relationships between JS variables and sprint performance. Eighteen male subjects with resistance training experience performed 2 sets of 4 JS with no extra load with the instructions to concentrate on (a) jumping for maximum height and (b) extending the legs as fast as possible to maximize explosive force. Sprint performance was assessed at 0- to 10-m and 10- to 20-m distances. From the JS jump height, peak power, relative peak power, peak force, peak velocity, and countermovement distance were measured from a force platform and position transducer system. The JS variables under the 2 instructions were compared with paired t -tests, and the relationships between these variables and sprint performance were determined with Pearson's correlations. The jump height instruction produced greater mean jump height and peak velocity ( p < 0.05), but the fast leg extension instruction produced greater ( p < 0.05) peak force (3.7%). There was a trivial difference between the instructions for peak power output ( p > 0.05). Jump height was the variable that correlated most strongly with 10-m time and 10- to 20-m time under both instructions. The height instruction produced a stronger correlation with 10-m time ( r = −0.455), but the fast leg extension JS produced a greater correlation with 10–20 time ( r = −0.545). The results indicate that instructions have a meaningful influence on JS variables and therefore need to be taken into consideration when assessing or training athletes.